Pengaruh Kompetensi Auditor, Pengalaman Auditor Dan Motivasi Auditor Terhadap Kualitas Audit (Studi Empiris Pada Auditor di Inspektorat Provinsi Banten) - Mazda Eko Sri Tjahjono; Dewi Robiatul Adawiyah (Jurnal Riset Akuntansi Terpadu, 2019)
This study aims to examine the effect of auditor competence, auditor experience and auditor motivation of audit quality. The sample in this research is 147 respondents with sampling technique using purposive sampling method that determines criteria according to the research needed with senior auditor in inspektorat provinsi banten area as respondents. The data are collected by distributing questionnaires to the respective respondents. The method of analysis is multiple regression analysis. The data in this research is processed by using software SPSS version 23 (Statistical Product and Service Solution). The results of this research reveals that auditor competence has significantly positive effect on audit quality, auditor experience has significanly positive effect on audit quality and auditor motivation has significantly positive effect on audit quality